2015
DOI: 10.1021/acs.jpclett.5b01896
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Isomer-Resolved Measurements of Sequential Addition of Acetylene to the Propargyl Radical

Abstract: Soot formation in combustion is a complex process in which polycyclic aromatic hydrocarbons (PAHs) are believed to play a critical role. Recent works concluded that three consecutive additions of acetylene (C2H2) to propargyl (C3H3) create a facile route to the PAH indene (C9H8). However, the isomeric forms of C5H5 and C7H7 intermediates in this reaction sequence are not known. We directly investigate these intermediates using time- and isomer-resolved experiments. Both the resonance stabilized vinylpropargyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…6(d)], several changes were made to the mechanism: We included the cyclization reactions of the benzyl radical with 1,3-butadiene and the 1,3-butadiene-1-yl radical (n-C 4 H 5 ) as proposed by Fascella et al [34] and the addition reaction of methyl to phenylacetylene (A1C2H) using a rate for a similar reaction from Marinov et al [27]. Furthermore, an indene formation pathway via cycloheptatriene suggested by Savee et al [35] was added but found not to contribute.…”
Section: Resultsmentioning
confidence: 99%
“…6(d)], several changes were made to the mechanism: We included the cyclization reactions of the benzyl radical with 1,3-butadiene and the 1,3-butadiene-1-yl radical (n-C 4 H 5 ) as proposed by Fascella et al [34] and the addition reaction of methyl to phenylacetylene (A1C2H) using a rate for a similar reaction from Marinov et al [27]. Furthermore, an indene formation pathway via cycloheptatriene suggested by Savee et al [35] was added but found not to contribute.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with the failure 7 of tunable PIMS to detect C 7 H 7 radicals as benzyl undergoes pyrolysis. Very recently, time-resolved PIMS spectroscopy was used 47 to study soot formation. The addition of acetylene to propargyl radical in a slow flow quartz reactor at (10 Torr/1000 K) was found to induce molecular weight growth via the sequence: HC≡≡CH + HCCCH 2 → C 5 H 5 → C 7 H 7 .…”
Section: Discussionmentioning
confidence: 99%
“…48 Trace amounts of l-C 5 H 5 also contribute to the threshold ion signal between 8.0 and 8.2 eV, and their involvement in the reaction pathways might also be noticeable in light of recent findings. 47,49 A mechanism for the formation of l-C 5 H 5 and the PIE curve showing some evidence is displayed in the ESI † ( Fig. S3 and S4).…”
Section: Mass Spectrometric Analysismentioning
confidence: 99%